Hypoxia-inducible protein 2 Hig2/Hilpda mediates neutral lipid accumulation in macrophages and contributes to atherosclerosis in apolipoprotein E-deficient mice - Maier, Anja; Wu, Hao; Cordasic, Nada; Oefner, Peter; Dietel, Barbara; Thiele, Christoph; Weidemann, Alexander; Eckardt, Kai-Uwe; Warnecke, Christina (The FASEB Journal, 2017)
Recently we identified hypoxia-inducible protein 2 (HIG2)/hypoxia-inducible lipid droplet associated (HILPDA) as lipid droplet (LD) protein. Because HILPDA is highly expressed in atherosclerotic plaques, we examined its regulation and function in murine macrophages, compared it to the LD adipose differentiation-related protein (Adrp)/perilipin 2 (Plin2), and investigated its effects on atherogenesis in apolipoprotein E-deficient (ApoE(-/-)) mice. Tie2-Cre-driven Hilpda knockout (cKO) did not affect viability, proliferation, and ATP levels in macrophages. Hilpda proved to be a target of hypoxia-inducible factor 1 (Hif-1) and peroxisome proliferator-activated receptors. In contrast, Adrp/Plin2 was not induced by Hif-1. Hilpda localized to the endoplasmic reticulum-LD interface, the site of LD formation. Hypoxic lipid accumulation and storage of oxidized LDL, cholesteryl esters and triglycerides were abolished in Hilpda cKO macrophages, independent of the glycolytic switch, fatty acid or lipoprotein uptake. Hilpda depletion reduced resistance against lipid overload and increased production of reactive oxygen species after reoxygenation. LPS-stimulated prostaglandin-E2 production was dysregulated in macrophages, demonstrating the substrate buffer and reservoir function of LDs for eicosanoid production. In ApoE(-/-) Hilpda cKO mice, total aortic plaque area, plaque macrophages and vascular Vegf expression were reduced. Thus, macrophage Hilpda is crucial to foam-cell formation and lipid deposition, and to controlled prostaglandin-E2 production. By these means Hilpda promotes lesion formation and progression of atherosclerosis.-Maier, A., Wu, H., Cordasic, N., Oefner, P., Dietel, B., Thiele, C., Weidemann, A., Eckardt, K.-U., Warnecke, C. Hypoxia-inducible protein 2 Hig2/Hilpda mediates neutral lipid accumulation in macrophages and contributes to atherosclerosis in apolipoprotein E-deficient mice.
EVALuna2:4018

Role of TGF-β in anti-rhinovirus immune responses in asthmatic patients - Bielor, Carina; Sopel, Nina; Maier, Anja; Blau, Ashley; Sharma, Himanshu; Vuorinen, Tytti; Kross, Bettina; Mittler, Susanne; Graser, Anna; Mousset, Stephanie; Melichar, Volker O.; Kiefer, Alexander; et al. (Journal of Allergy and Clinical Immunology, 2017)
EVALuna2:32796

The activating protein 1 transcription factor basic leucine zipper transcription factor, ATF-like (BATF), regulates lymphocyte- and mast cell-driven immune responses in the setting of allergic asthma - Ubel, Caroline; Sopel, Nina; Graser, Anna; Hildner, Kai; Reinhardt, Cornelia; Zimmermann, Theodor; Rieker, Ralf Joachim; Maier, Anja; Neurath, Markus; Murphy, Kenneth M.; Finotto, Susetta (Journal of Allergy and Clinical Immunology, 2014)
Mice without the basic leucine zipper transcription factor, ATF-like (BATF) gene (Batf(-/-)) lack TH17 and follicular helper T cells, which demonstrates that Batf is a transcription factor important for T- and B-cell differentiation.In this study we examined whether BATF expression would influence allergic asthma.In a cohort of preschool control children and children with asthma, we analyzed BATF mRNA expression using real-time PCR in PBMCs. In a murine model of allergic asthma, we analyzed differences in this allergic disease between wild-type, Batf transgenic, and Batf(-/-) mice.In the absence of corticosteroid treatment, children with recurrent asthma have a significant increase in BATF mRNA expression in their PBMCs. Batf(-/-) mice display a significant reduction in the pathophysiologic responses seen in asthmatic wild-type littermates. Moreover, we discovered a decrease in IL-3 production and IL-3-dependent mast cell development in Batf(-/-) mice. By contrast, IFN-? was induced in lung CD4(+) and CD8(+) T cells. Intranasal delivery of anti-IFN-? antibodies induced airway hyperresponsiveness and inflammation in wild-type but not in Batf(-/-) mice. Transgenic overexpression of Batf under the control of the CD2 promoter/enhancer augmented lung inflammation and IgE levels in the setting of experimental asthma.BATF is increased in non-steroid-treated asthmatic children. Targeting BATF expression resulted in amelioration of the pathophysiologic responses seen in children with allergic asthma, and BATF has emerged as a novel target for antiasthma interventions.
EVALuna2:1742